Substitution of Ba for Ca in the Structure of CaAl12O19. Issue 1 (12th September 2016) - Chen, Junhong; Chen, Haiyang; Mi, Wenjun; Cao, Zheng; Li, Bin; Liang, Chaojing
Abstract : The effect of Ba 2+ on the crystallization thickness of calcium hexaaluminate (CA6 ) along the c axis was studied. The results show that after introduction of Ba 2+, the CA6 flake crystals fired at 1600°C become thicker obviously. The structure refinement shows that the structure formula of the doped CA6 is (Ca0.973 Ba0.027 )O·6Al2 O3, indicating Ba 2+ has entered the lattices of CA6 and substituted Ca 2+ in the mirror layers. The introduction of Ba 2+ results in more defects VA l in spinel block layers in CA6, making ions easier to diffuse along c axis and fastening the growing of CA6 crystals along c axis. Thus, the introduction of Ba 2+ is feasible and advantageous to increase the crystallization thickness of CA6 along c axis.